2021
DOI: 10.3390/pathogens10020216
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Morphometric and Molecular Approach to Update the Impact and Distribution of Potato Cyst Nematodes Globodera rostochiensis and Globodera pallida (Tylenchida: Heteroderidae) in Algeria

Abstract: Morphological and molecular studies were conducted to characterize the specific identity of 36 isolates of potato cyst nematodes (PCNs) recovered from soil samples collected in several potato producing areas of Algeria. Morphometric data revealed that 44% of isolates contained Globodera pallida alone, 28% contained Globodera rostochiensis alone and 28% mixtures of the two species. Morphometric values of cysts and second-stage juveniles were generally distributed with slight differences in the expected ranges f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The detection of the target species within pools of non-target species was attempted because it was previously demonstrated that G. pallida and G. rostochiensis cohabit in mixed populations in potato fields [52,56]. Samples of pure G. pallida and pure G. rostochiensis were not used since the specificity had been previously demonstrated.…”
Section: Diagnostic Sensitivitymentioning
confidence: 99%
“…The detection of the target species within pools of non-target species was attempted because it was previously demonstrated that G. pallida and G. rostochiensis cohabit in mixed populations in potato fields [52,56]. Samples of pure G. pallida and pure G. rostochiensis were not used since the specificity had been previously demonstrated.…”
Section: Diagnostic Sensitivitymentioning
confidence: 99%
“…In reality, gPCN has been reported to occur together with pPCN in many areas. For example, 25% of the infested fields in England and Wales were detected with both nematode species, while the proportion was 28% in Algeria 7 , 8 . In Newfoundland (Canada), Portugal, and Kenya, gPCN was also accompanied by pPCN in some fields 11 , 14 , 16 .…”
Section: Discussionmentioning
confidence: 98%
“…Minnis et al were the first to report a detailed field survey of PCNs in the United Kingdom, which identified severe infestation of both gPCN and pPCN 7 . In recent years, countries in most global regions have confirmed the presence of PCNs; these included Portugal, Turkey, Algeria, Morocco, India, Indonesia, Australia, Colombia, Kenya, Canada and USA 8 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Surveys conducted from 1990s until today confirmed the distribution of PCN in most of potato producing regions (Masters and Engineering non published works; Djebroune, 2019;Benttoumi et al, 2020;Berrahia and Sellami, 2022). Both species Globodera pallida and G. rostochiensis occur in Algeria (Tirchi et al, 2016;Djebroune et al, 2021).…”
Section: Main Plant Parasitic Nematodes Reported In Algeriamentioning
confidence: 99%